PENERAPAN PASAL 31 KITAB UNDANG UNDANG HUKUM PIDANA TENTANG PENANGGUHAN PENAHANAN DI KEPOLISIAN RESOR POHUWATO - Herlina Sulaiman; Devriani Lasiki (IAIN Ambon, 2020)
The implementation of the suspension of detention has been regulated in article 31 of the Criminal Procedure Code. Suspension of detention is not only given in mild cases but can be given in severe cases. Suspension of detention as a right of the suspect must get more attention from the right of the assignment is more than based on objectives that can be done based on the subjective. The objector must be protected by the Detention Suspension because not only the image of the investigator is at stake but the image of the police force as law enforcement will also be in the spotlight. The assessment of deferral assistance does not only look at the interests of the Criminal Procedure Code but must also take into account the interests of court suspects. Therefore the suspension of detention is not a tool used by suspects to be used temporarily in the education process. Keywords: Suspension of detention, suspects, imprisonment